Odpowiedź :
Odpowiedź:
(x-2)²=(6+x)*(3x-6)
x²-4x+4=18x-36+3x²-6x
3x²-x²+12x+4x-36-4=0
2x²+16x-40=0 /:2
x²+8x-20=0 Δ= 64+ 80= 144 √Δ=12
x1=(-8-12)/2= - 10 x2=(-8+12)/2= 2
dla x= -10 to wyrazy :
6-10=-4 -10-2=-12 3*(-10) -6= -36 = c. malejacy
dla x= 2 to wyrazy :
6+2=8 2-2=0 3*2-6= 0= sprzeczne
odp.
x= -10
Szczegółowe wyjaśnienie:
Odpowiedź:
jeśli mamy ciąg geometryczny i wyrazy x,y,z to y do kwadratu musi się równać x razy z więc:
[tex](x-2)^{2}=(6+x)(3x-6)[/tex]
[tex]x^{2}-4x+4=18x-36+3x^{2}-6x[/tex]
[tex]x^{2}-4x+4=3x^{2}+12x-36[/tex]
[tex]-2x^{2}-16x+40=0[/tex]
delta=[tex](16)^{2}+320[/tex]
delta=256+320=576
[tex]\sqrt{576} =24[/tex]
x1=[tex]\frac{16-24}{-4} =2[/tex]
x2=[tex]\frac{16+24}{-4} =-10[/tex]
x=2 lub -10
podstawmy pod 2
6+2=8
2-2=0
6-6=0
podstawmy pod -10
6-10=-4
-10-2=-12
-30-6=-36
czyli x=-10
Szczegółowe wyjaśnienie: